Predictors of in-hospital mortality in patients admitted with congestive Heart failure (HF) in a general medical ward – A case-control study from a tertiary care centre in South India - Faith Mariam John (Wolters Kluwer Medknow Publications, 2021)
Background and Objectives: Studies around the world have shown that incidence of HF is increasing with the highest risk of mortality during their first admission and in the subsequent 1 year. Only a few Indian studies had looked at the predictors of in-hospital mortality in patients admitted with HF in patients admitted in medical wards. We have done a case control study to determine the risk factors for in-hospital mortality, in patients admitted with HF, in general medical ward, in a tertiary care centre in south India. Methods: We collected demographic data, clinical details and outcome data from case records. We performed a univariate analysis comparing those who died as compared to those who did not. Factors that were significant in the above, were entered into a logistic regression analysis to identify factors that independently predicted poor outcomes. Results: The in-hospital mortality rate in patients admitted with HF was 12.19%. On multivariate analysis, Systolic blood pressure < 115 mmHg {OR – 2.82, CI (1.29 – 6.19)}, serum lactate > 2 mmol/l {OR-2.61, CI (1.16 – 5.87)}, and GCS < 15 {OR 6.64, CI (2.26 – 19.51)} were statistically significant. Conclusion: Our study has shown that, in patients admitted with HF in general medical ward, at admission, low systolic blood pressure, high serum lactates, low GCS were predictors of in-hospital mortality.